Três ensaios de bioética (SciELO - Editora FIOCRUZ, 2015)
Readers interested in the theoretical development of bioethics and, at the same time, in its application to the solution of moral conflicts will certainly find material of great value in this book. Each chapter places bioethics in a different context: in clinical, genomics and biosafety. In the first essay, the possibilities of this 'toolbox' called bioethics are discussed to understand and try to resolve conflicts of interests and values ​​in the context of relationships between professionals and users of health services. In the second, the author applies the tools of bioethics to the case of moral conflicts involving genomics, contemplating arguments for and against genetic engineering practices and contributing to critical and unprejudiced reasoning on the subject. Finally, the third chapter deals with the interface between bioethics and biosafety, which have common concerns, such as the issue of risks, but different approaches - while bioethics deals with moral values, biosafety makes use of technical, administrative and cool.